A case of dual left anterior descending artery with myocardial infarction - Abhaykumar Binodkumar Dheeraj; Sandeep Kumar Giri; Pankaj Suresh Ghormade (University of São Paulo, 2021)
The Left anterior descending artery (LAD) is a branch of the left main coronary artery which runs obliquely towards the apex of the heart in the anterior interventricular sulcus. Among all of the coronary arteries, the LAD artery has the most constant course. Amongst the anomalies of coronaries, the duplication or bifurcation of the LAD artery is infrequent. The classification of the bifurcation of the LAD has been extensively described in various reports with the widespread use of CT Angiography. We describe herein, an anomalous LAD detected on autopsy. This unusual case highlights the gross autopsy finding of Type-I anomalous dual LAD coronary artery in a young adult who died of Myocardial Infarction.